2021
DOI: 10.1038/s41598-021-85295-2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA miR-542-3p suppresses decidualization by targeting ILK pathways in human endometrial stromal cells

Abstract: Decidualization of human endometrial stromal cells (HESCs) is a vital step for successful pregnancy. However, the process by which micro-RNAs (miRNAs) regulate decidualization remains elusive. Our current study was designed to identify the mechanism of miRNA miR-542-3p and its potential targets in regulating decidualization. The results showed that miR-542-3p was down-regulated in HESCs. Luciferase assay confirmed that integrin-linked kinase (ILK) is a direct target of miR-542-3p. Overexpression of miR-542-3p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This result is important in terms of the ability of ectopic endometrial stromal cells to decidualize. It has been postulated that the overexpression of miR-542-3p inhibits the process of differentiation (decidualization) of endometriotic stromal cells [ 72 , 73 , 74 ] and the proliferation of human endometrial stromal cells [ 75 ]. An important result from our study is the observation of a positive, albeit statistically insignificant, correlation between miR-542-3p expression and the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This result is important in terms of the ability of ectopic endometrial stromal cells to decidualize. It has been postulated that the overexpression of miR-542-3p inhibits the process of differentiation (decidualization) of endometriotic stromal cells [ 72 , 73 , 74 ] and the proliferation of human endometrial stromal cells [ 75 ]. An important result from our study is the observation of a positive, albeit statistically insignificant, correlation between miR-542-3p expression and the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…miR-194-3p has also been reported to have a relationship with decidualization via the downregulation of PGR [ 29 ]. Recently, Qu et al have reported that miR-542-3p inhibits decidualization through the downregulation of the ILK pathway [ 30 ]. In our study, miR-375 was found to be a negative regulator of decidualization in HESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many miRNAs’ functions were explored in pregnancy-related cellular and animal models. Downregulation of miR-542-3p in human ESCs facilitated ESCs decidualization by activating integrin-linked kinase ( ILK )/transforming growth factor (TGF)-β1/SMAD family member 2 signaling pathway and induced loss of embryo implantation in a mouse model of early pregnancy [10] . Conversely, a decreased expression of miRNA-155-5p in decidua tissue not only promoted proliferation but also inhibited apoptosis of decidua stromal cells by inhibiting the nuclear factor kappa B signaling pathway, which could maintain normal pregnancy [11] .…”
Section: Mirnas Lncrnas and Circrnas In The Establishment And Mainten...mentioning
confidence: 99%